Mediating role of social support in relations between psychological capital and subjective well-being among IDF soldiers during conflict: insights from the 2023 Gaza war - Batel Hazan-Liran; Ofra Walter (Israel Journal of Health Policy Research)
Abstract Background The study explored the relations between psychological capital, social support, and subjective well-being among Israel Defense Forces soldiers, focusing on differences between active-duty and reserve soldiers, as well as pre-war and wartime conditions. Methods The sample comprised 233 soldiers, divided into three groups based on their service conditions: active-duty soldiers before the war, active-duty soldiers during the war, and reserve soldiers during the war. Four questionnaires were administered: Demographic Questionnaire, Psychological Capital Questionnaire, Social Support Questionnaire, and Subjective Well-Being Questionnaire. Results The findings revealed significant positive correlations between psychological capital, social support, and subjective well-being, with social support mediating relations. While psychological capital remained stable across various service conditions, social support and subjective well-being were more pronounced among soldiers serving during wartime, underscoring the vital role of interpersonal connections in high-stress environments. Conclusion The results suggest psychological capital may function as a psychological buffer, positively associated with resilience and well-being. Moreover, the mediation effect of social support highlights the importance of social networks in sustaining psychological resilience and mitigating the adverse effects of combat stress. While these are established constructs, the study embeds them within a real-time war context, offering rare insight into how they operate under acute national trauma. Given the cross-sectional design, findings should be interpreted as associations rather than definitive causal relationships.